SERUM LIPIDS : NEW BIOLOGICAL MARKERS IN DEPRESSION ? - Khalid, Abdul (Medknow Publications, 1998)
Several studies suggest that a low cholesterol concentration is associated with depression. The authors sought to determine whether an association exists between serum lipid concentrations and depression. 28 drug-naive patients of major depression diagnosed according to DSMlll- R criteria were included in the study and severity of depression was measured on Hamilton Rating Scale for Depression. Suicidal intent was assessed on Suicidal Intent Questionnaire. 28 normal healthy controls were selected and matched for age, sex and body-mass index with the depressives. Serum lipid estimations were done in each subject after 12 hours overnight fasting. The main finding of the study is that total serum cholesterol, serum triglycerides and serum LDL cholesterol are decreased while serum HDL cholesterol is increased in depression and these changes were more marked in depressed subjects with definite suicidal intent. On regression analysis, total serum cholesterol was the most important predictive variable of the severity of depression.